Extraosseous Calcifying Odontogenic Cyst Initially Interpreted as a Parulis - Karla Lizeth Santana-Arenas; Israel Guardado-Luevanos; Miguel Padilla-Rosas; Mario Nava-Villalba (Hindawi Limited, 2024)
Extraosseous variants of odontogenic cysts are an infrequent clinical finding, although they have a relatively indolent biological behavior compared to their intraosseous counterparts; due to their nature and clinical appearance, these lesions can be confused with multiple entities that affect soft tissues, so their diagnosis can only be achieved through surgical removal and subsequent histopathological analysis. The extraosseous/peripheral variant of calcifying odontogenic cyst (E/PCOC) has a heterogeneous clinical presentation mainly in terms of size and involvement or not of adjacent anatomical structures such as bone and teeth; in addition, there are few cases reported to date; thus, there are still clinical features to be elucidated. This report presents a child affected by E/PCOC in an unusual location, as well as its therapeutic management, which at first time was suspected of endodontic nature, due to a history of dental trauma.